Illuminating Two Secondary Schoolteachers’ Praxes on a ‘terrain of freedom:’ Lessons for Teacher Education - Paul Tarc; Nicholas Ng-A-Fook; Tasha Ausman; Catherine James (Northwest Journal of Teacher Education, 2025)
This paper attunes to the stated focus of this special issue—teacher subjectivities on a terrain of freedom—to consider the qualities, possibilities and limits of teachers’ praxes and development upon this ‘terrain.’ In response to the call, we explore three critical questions: 1) Where does the teacher’s freedom lie amidst required protocols and standardization?; 2) Can teachers transcend how they have been conceived and conditioned?; and 3) How can teachers engage in transformative development? Through a "poetics of teaching," inspired by Hansen (2004), we frame teaching as a curricular and pedagogical art form that melds interdisciplinary, intellectual, aesthetic, and moral dimensions to enrich the professional and personal livelihoods of teachers and, in turn, students. This approach supports UNESCO's (2021) principles of lifelong professional learning and the nurturing of the different global and local ecosystems that connect to our K-12 classrooms. Drawing on empirical research from a pilot study, this article highlights the transformative practices of two secondary school teachers as they navigate and expand upon their professional “terrain of freedom,” demonstrating different institutional possibilities and constraints. Our findings suggest that teacher education programs should cultivate environments that encourage innovation, critical reflection, and ethical engagement, aligning with UNESCO’s calls for a new social contract that advocates for teachers as agents of change in reimagining education for more just and sustainable futures. These lessons learned from our pilot study underscore the need, as we suggest, for teacher education to nurture, support, and sustain professional educators capable of transforming curriculum, their pedagogical, and classroom communities toward and on behalf of the public good.